The energy-irrigation nexus and its impact on groundwater markets in eastern Indo-Gangetic basin: Evidence from West Bengal, India - Mukherji, Aditi (2007)
South Asia in general and India in particular is heavily dependent on groundwater for supporting its largely agrarian population. Informal pump irrigation services markets have played an important role in providing access to irrigation to millions of small and marginal farmers and had positive equity, efficiency and sustainable impacts in water-abundant regions such as West Bengal. Quite predictably, in such pump lift-based economy, fortunes of energy and irrigation sectors are closely entwined. This has often been called the 'energy-irrigation' nexus. There are two major sources of energy for pumping groundwater, viz. electricity and diesel. Most of the current discourse in the field has looked only at the 'electricity-irrigation' nexus to the exclusion of the 'diesel-irrigation nexus'. This paper looks at both these aspects. In doing so, it makes two propositions. First, high flat-rate electricity tariff encourages development of water markets whereby the water buyers?who are mostly small and marginal farmers?benefit through access to irrigation. Second, low rate of rural electrification has forced majority of farmers to depend on diesel for groundwater pumping and the steep increase in diesel prices over the last few years has resulted in economic scarcity of groundwater. This in turn has had serious negative impacts on crop production and farm incomes. Using primary field data from West Bengal, India, this paper makes a case for rapid rural electrification and continuation of high flat-rate tariff, which would in turn support developed groundwater markets and provide access to irrigation to the poor and marginal farmers.